Correlation of the Risk Factors in Degenerative Lumbar Spondylolisthesis with MRI Imaging - Paulus Rahardjo; Harry Wahyudhy Utama; Rosy Setiawati; Damayanti Tinduh (Malaysian Journal of Medicine and Health Sciences, 2023)
Introduction: Degenerative spondylolisthesis burdens the future economy. Elderly individuals with this condition suffer from back pain, limb paralysis, reduced activity, and diminished quality of life. Surgery offers relief but is risky and expensive. As healthcare improves, the aging population grows, and spondylolisthesis incidence rises. Early detection and risk factor management are vital for prevention. Therefore, this study aimed to evaluate the correlation of the risk factors for degenerative lumbar spondylolisthesis. Methods: A retrospective observational study was done in Dr Soetomo General Academic Hospital, Surabaya from January 2018 to December 2019. Forty-five subjects with degenerative spondylolisthesis diagnosed by MR Imaging enrolled in this study. Intervertebral disc, facet joint, multifidus muscle, and ligamentum flavum at level L1 until level L5 were examined using MR imaging. Correlation analysis was measured using the Spearman correlation test and risk factor analysis was measured using the logistic regression test. Results: There are significant correlations between intervertebral disc degeneration, facet joint osteoarthritis, multifidus muscle fatty infiltration, and thickening of ligamentum flavum with degenerative spondylolisthesis. The risk factors at levels L3-4 and L5-S1 are intervertebral disc degeneration and L4-5 is multifidus muscle fatty infiltration and facet joint osteoarthritis. Conclusion: This study confirmed the risk factors that correlated with degenerative lumbar spondylolisthesis.